The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1148/radiology.194.2.7824721
|View full text |Cite
|
Sign up to set email alerts
|

CT assessment of bronchi in sarcoidosis: endoscopic and pathologic correlations.

Abstract: Bronchial involvement in sarcoidosis was detected at CT in 65% of cases. CT can help predict whether bronchial granulomas will be found in cases of sarcoidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 0 publications
1
50
0
3
Order By: Relevance
“…Mural thickening, endobronchial involvement, extrinsic compression from enlarged lymph nodes, and architectural distortion of the airway can all lead to bronchial stenosis. Bronchoscopy is a useful tool identifying tracheobronchial stenosis [12,13]. In the present study, bronchial stenosis was found in 57.2% (n=36) of our patients.…”
Section: Discussionsupporting
confidence: 55%
“…Mural thickening, endobronchial involvement, extrinsic compression from enlarged lymph nodes, and architectural distortion of the airway can all lead to bronchial stenosis. Bronchoscopy is a useful tool identifying tracheobronchial stenosis [12,13]. In the present study, bronchial stenosis was found in 57.2% (n=36) of our patients.…”
Section: Discussionsupporting
confidence: 55%
“…Bronchial involvement, as judged by regular or irregular mural thickening and luminal narrowing, is detected on CT in 65% of patients and is usually concordant with endoscopic findings and endobronchial mucosal granulomas [37]. CT can also demonstrate extrinsic or intrinsic stenosis (see later in this review), traction bronchectasis and bronchial distortion ( fig.…”
Section: Airway Involvementmentioning
confidence: 68%
“…CT as an aid to obtaining biopsy/cytology material There is a clear association between bronchial abnormalities seen on CT and the presence of mucosal granulomas on endobronchial biopsy [37]. Similarly, DE BOER et al [38] recently demonstrated that the total extent of parenchymal disease on CT in addition to the pattern and lobar distribution, i.e.…”
Section: Diagnostic Contribution Of Ctmentioning
confidence: 98%
See 2 more Smart Citations